Problem based learning information system / Nicholas Barau Eddy - Nicholas , Barau Eddy (2003)
The Problem Based Learning information system is an Internet based system developed for use in Faculty of Computer Science and Information Technology, University Malaya, to help facilitate and manage Problem Based Learning Courses. This system helps both lecturers and students in their Problem Based Learning related work and offers a better student and lecturer interaction. The system is also capable of managing reports, assignment submission, evaluation tools, forum capability and online grading. The Problem Based Learning information system is developed with PHP on the Microsoft Windows NT Server platform utilizing database created and stored in MySQL. The system was developed taking in to considerations in using open-source and is believed that the system of this nature will gradually become and essential in the future.